YY1-induced upregulation of LncRNA-ARAP1-AS2 and ARAP1 promotes diabetic kidney fibrosis via aberrant glycolysis associated with EGFR/PKM2/HIF-1α pathway - Li, Xin; Ma, Tian-Kui; Wang, Min; Zhang, Xiao-Dan; Liu, Tian-Yan; Liu, Yue; Huang, Zhao-Hui; Zhu, Yong-Hong; Zhang, Shuang; Yin, Li; Xu, Yan-Yan; Ding, Hong; et al. (Frontiers in Pharmacology, 2023)
Objectives: Dimeric pyruvate kinase (PK) M2 (PKM2) plays an important role in promoting the accumulation of hypoxia-inducible factor (HIF)-1α, mediating aberrant glycolysis and inducing fibrosis in diabetic kidney disease (DKD). The aim of this work was to dissect a novel regulatory mechanism of Yin and Yang 1 (YY1) on lncRNA-ARAP1-AS2/ARAP1 to regulate EGFR/PKM2/HIF-1α pathway and glycolysis in DKD. Materials and methods: We used adeno-associated virus (AAV)-ARAP1 shRNA to knocked down ARAP1 in diabetic mice and overexpressed or knocked down YY1, ARAP1-AS2 and ARAP1 expression in human glomerular mesangial cells. Gene levels were assessed by Western blotting, RT-qPCR, immunofluorescence staining and immunohistochemistry. Molecular interactions were determined by RNA pull-down, co-immunoprecipitation, ubiquitination assay and dual-luciferase reporter analysis. Results: YY1, ARAP1-AS2, ARAP1, HIF-1α, glycolysis and fibrosis genes expressions were upregulated and ARAP1 knockdown could inhibit dimeric PKM2 expression and partly restore tetrameric PKM2 formation, while downregulate HIF-1α accumulation and aberrant glycolysis and fibrosis in in-vivo and in-vitro DKD models. ARAP1 knockdown attenuates renal injury and renal dysfunction in diabetic mice. ARAP1 maintains EGFR overactivation in-vivo and in-vitro DKD models. Mechanistically, YY1 transcriptionally upregulates ARAP1-AS2 and indirectly regulates ARAP1 and subsequently promotes EGFR activation, HIF-1α accumulation and aberrant glycolysis and fibrosis. Conclusions: Our results first highlight the role of the novel regulatory mechanism of YY1 on ARAP1-AS2 and ARAP1 in promoting aberrant glycolysis and fibrosis by EGFR/PKM2/HIF-1α pathway in DKD and provide potential therapeutic strategies for DKD treatments.